Reducing Glutamate Uptake in Rat Hippocampal Slices Enhances Astrocytic Membrane Depolarization While Down-Regulating CA3–CA1 Synaptic Response - Srivastava, Ipsit; Vazquez-Juarez, Erika; Lindskog, Maria (Frontiers in Synaptic Neuroscience, 2020)
The majority of synaptic activity in the brain consists of glutamatergic transmission, and there are numerous mechanisms, both intra- and inter-cellular that regulate this excitatory synaptic activity. Importantly, uptake of glutamate plays an important role and a reduced level of astrocytic glutamate transporters affect the normally balanced neurotransmission and is observed in many mental disorders. However, reduced glutamate uptake affects many different synaptic mechanisms in the astrocyte as well as in the neuron, and the effects are challenging to delineate. Combining electrophysiological recordings from neurons and astrocytes as well as extracellular glutamate recordings in rat hippocampal slices, we confirmed previous work showing that synaptic stimulation induces a long-lasting depolarization of the astrocytic membrane that is dependent on inward-rectifier potassium channels. We further showed that when glutamate transporters are blocked, this astrocytic depolarization is greatly enhanced although synaptic responses are reduced. We propose that increasing the levels of synaptic glutamate through blocking glutamate transporters reduces the AMPA-mediated synaptic response while the NMDA receptor current increases, contributing to a rise in extracellular K+ leading to enhanced astrocytic depolarization.